The Effect of Pentahelix Collaboration on Tourism Development of West Sumbawa Regency - Anas Pattaray; Nanda Nipri (ijd-demos, 2022)
AbstractWest Sumbawa Regency is decadent with natural and cultural tourism potential. West Sumbawa has beauty and provides opportunities for the tourism industry. However, this potential has not been managed optimally, so tourism business activities, especially product marketing, have not found the right formula. One of the efforts that need to be made is the partnership and collaboration of tourism stakeholders. This study examines how much influence stakeholder partnerships have on the marketing of tour packages in the West Sumbawa Regency. The primary stakeholder partnership was studied using a descriptive quantitative approach with multiple regression data analysis methods. This study found that the correlation of stakeholders with the marketing of tour packages has a value of 57.2%. Simultaneously, stakeholders influence the marketing of tour packages significantly by 62.1%. Meanwhile, the tourism association variable as a private stakeholder has a high percentage of 46.6% of its influence on tourism package marketing.Keywords: West Sumbawa, Tour Packages, Partnership. AbstrakKabupaten Sumbawa Barat dianugerahi dengan potensi wisata alam dan budaya. Sumbawa Barat memiliki keindahan dan memberikan peluang bagi industri pariwisata. Namun potensi tersebut belum dikelola secara optimal, sehingga kegiatan usaha pariwisata khususnya pemasaran produk belum menemukan formula yang tepat. Salah satu upaya yang perlu dilakukan adalah kemitraan dan kolaborasi para pemangku kepentingan pariwisata. Penelitian ini mengkaji seberapa besar pengaruh kemitraan pemangku kepentingan terhadap pemasaran paket wisata di Kabupaten Sumbawa Barat. Kemitraan pemangku kepentingan utama dipelajari dengan menggunakan pendekatan kuantitatif deskriptif dengan metode analisis data regresi berganda. Penelitian ini menemukan bahwa korelasi stakeholder dengan pemasaran paket wisata memiliki nilai sebesar 57,2%. Secara simultan stakeholder mempengaruhi pemasaran paket wisata secara signifikan sebesar 62,1%. Sedangkan variabel asosiasi pariwisata sebagai private stakeholder memiliki persentase pengaruh yang tinggi sebesar 46,6% terhadap pemasaran paket wisata.Kata kunci: Sumbawa Barat, Paket Wisata, Kemitraan.